Diabetes Mellitus, Extreme Insulin Resistance, and Hypothalamic-Pituitary Langerhans Cells Histiocytosis. (23rd June 2019) - Sollier, Mathilde; Halbron, Marine; Donadieu, Jean; Idbaih, Ahmed; Cohen Aubart, Fleur; Vigouroux, Corinne; Auclair, Martine; Bourron, Olivier; Bastin, Marie; Béra, Géraldine; Touraine, Philippe; Young, Jacques; et al.
Abstract : Background . Langerhans Cell Histiocytosis (LCH) is a rare inflammatory neoplasm characterized by an infiltration of organs by Langerin + (CD207+) and CD1a+ histiocytes. Diabetes insipidus is a frequent manifestation of the disease, while diabetes mellitus is very rare. We report the first case of a 20-year-old man suffering from hypothalamopituitary histiocytosis and diabetes mellitus with serum anti-insulin receptor antibodies. Case Presentation . A 20-year-old patient was admitted for the evaluation of growth delay and hyperphagia. HbA1c level and fasting blood glucose were in the normal range. The diagnosis of hypothalamopituitary histiocytosis was based on histological features after biopsy of a large suprachiasmatic lesion identified on magnetic resonance imaging (MRI). Association of vinblastine and purinethol was started followed by a second-line therapy by cladribine. During the follow-up, the patient was admitted for recurrence of hyperglycemic states and extreme insulin resistance. The screening for serum anti-insulin receptor antibodies was positive. Each episode of hyperglycemia appeared to be correlated with tumoral activity and increase in serum anti-insulin receptor antibodies and appeared to be improved when the disease was controlled by chemotherapy. Conclusion . We report the first description of a hypothalamopituitary histiocytosis associated with serum anti-insulin receptor antibodies, extreme insulin resistance, and diabetes. Parallel evolution of glucose levels and serum anti-insulin receptor antibodies seemed to be the consequence of immune suppressive properties of cladribine.